2023
DOI: 10.3390/plants12142691
|View full text |Cite
|
Sign up to set email alerts
|

Flowered Grain Quality and Phytochemical Content of Non-Conventional Maize Hybrids from the Mexican Subtropics across Three Growing Cycles

Abstract: Development of non-conventional hybrids responds to the demand for the Elotes Occidentales land-race for production of pozole. The effect of growing cycle (2019, 2020, and 2021) on physical characteristics, flowered grain quality, and phytochemical content of two non-conventional hybrids of pozolero maize, as well as the effect of the presence or absence of pedicel, type of pollination (open and controlled, 2019), and parents (female and male, 2020) on flowered grain quality and content of phytochemical compou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Studies have revealed that up to 82% of anthocyanins are lost during nixtamalization [44]. However, in hybrids derived from the Elotes Occidentales landrace, it has been reported that anthocyanin losses from raw grain to flowered grain range from 48 to 68% [33], as traditional nixtamalization retains the aleurone layer (Fig. 3).…”
Section: Flowered Grain Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed that up to 82% of anthocyanins are lost during nixtamalization [44]. However, in hybrids derived from the Elotes Occidentales landrace, it has been reported that anthocyanin losses from raw grain to flowered grain range from 48 to 68% [33], as traditional nixtamalization retains the aleurone layer (Fig. 3).…”
Section: Flowered Grain Qualitymentioning
confidence: 99%
“…The Cacahuacintle landrace is recognized as the best one for pozole, given the quality and yield of the dish [30], and over the years it has been the most studied in terms of its technological characterization during nixtamalization [25,26,31,32]. However, very recently more research has been done using other landraces, such as Ancho, Bofo Harinoso de ocho, Bolita, Chalqueño, Cónico, Jala, Tabloncillo, Tuxpeño [24] and Elotes Occidentales [21,33]. Nevertheless, little is known about its sensory acceptance and consumer preferences.…”
Section: Introductionmentioning
confidence: 99%